An ethnobotanical study of medicinal plants used by the Nandi people in Kenya - Jeruto, Pascaline; Lukhoba, Catherine; Ouma, George; Ochuodho, Dennis O.; Mutai, Charles (Elsevier, 2007)
Ethnopharmacological relevance The study of local knowledge about natural resources is becoming increasingly important in defining strategies and actions for conservation or recuperation of residual forests. Aims of the study This study therefore sought to collect information from local populations concerning the use of Nandi Forest medicinal plants; verify the sources of medicinal plants used and determine the relative importance of the species surveyed. Materials and methods Data was obtained using semi-structured forms to record the interviewee's personal information and topics related to the medicinal use of specific plants. A total of 40 medicinal plants used locally for the treatment and/or control of human ailments were collected through interviews conducted with selected traditional doctors and professional healers. Results This study demonstrated that local people tend to agree with each other in terms of the plants use and that leaf material form the major component of plant parts exploited. The other harvested materials consist of stem bark, the roots and the whole plant, though at a lower intensity for making liquid concoctions from different plants. Majority of the remedies were prepared from a single species. In most cases, the mode of administration was oral. In the forest, some of the plants collected were scarce. This scarcity was attributed to indiscriminate logging, overexploitation, poor harvesting methods and current agricultural trends. Conclusion Conservation procedures and creation of awareness were identified as the main remedies to the current situation.
Keywords: Ethnobotany; Kenya medicinal plants; Nandi people